Internet-Administered Emotional Awareness and Expression Therapy for Somatic Symptom Disorder With Centralized Symptoms: A Preliminary Efficacy Trial - Maroti, Daniel; Ek, Josefine; Widlund, Rose-Marie; Schubiner, Howard; Lumley, Mark A.; Lilliengren, Peter; Bileviciute-Ljungar, Indre; Ljótsson, Brjánn; Johansson, Robert (Frontiers in Psychiatry, 2021)
Background: There is growing evidence that trauma, psychosocial conflict, and difficulties with emotional processing contribute to Somatic Symptom Disorder (SSD). Emotional Awareness and Expression Therapy (EAET) was developed to address these processes in SSD, and EAET has shown efficacy in face-to-face formats. No trial of an internet-delivered EAET (I-EAET) exists, however, so we developed such an intervention and conducted an uncontrolled feasibility and potential efficacy trial of I-EAET for SSD. Method: After screening potential participants, a sample of 52 patients (50 women, 2 men; age M = 49.6, SD = 11.9) with SSD initiated treatment. I-EAET consisted of nine weekly modules, focusing on psychoeducation, emotional awareness and exposure, and anxiety regulation with self-compassion. Therapists communicated with each patient by email for about 20 minutes per week during treatment, answering questions and giving feedback on homework assignments. Patients completed measures of somatic symptoms, depression, anxiety, trauma-related symptoms, and functional disability before treatment and again at post-treatment and 4-month follow-up. Results: A large reduction in somatic symptoms (PHQ-15) was observed for pre-to post-treatment (d = 1.13; 95% CI: 0.84-1.47) which was maintained at 4-month follow-up (d = 1.19; 95% CI: 0.88- 1.56). 23% of the patients at post-treatment and 27% at follow-up achieved a 50% or greater reduction in somatic symptoms. In addition, at post-treatment, there were small to medium magnitude (d’s from 0.33 to 0.72) reductions in anxiety (GAD-7), depression (PHQ-9), trauma-related symptoms (PCL-5), and functional disability (Sheehan Disability Scale). For all secondary outcome measures, improvements were slightly to substantially larger at follow-up than at post-treatment (d’s from 0.46 to 0.80). Conclusion: I-EAET appears to be a feasible treatment for adults with SSD. It results in substantial improvements not only in somatic symptoms but in other psychiatric symptoms and functioning, and these effects may rival those found in face-to-face EAET. A controlled trial is needed determine the effects of I-EAET specifically, and whether this approach might be superior to other internet-delivered treatments. Research should also identify treatment responders and mechanisms of change in EAET. Registered with clinicaltrials.gov with registration ID NCT04122846